Rezum: a new transurethral water vapour therapy for benign prostatic hyperplasia. Issue 11 (November 2018) - Westwood, Jennifer; Geraghty, Robert; Jones, Patrick; Rai, Bhavan P.; Somani, Bhaskar K.
Rezum is a minimally invasive transurethral water vapour therapy for benign prostatic enlargement which uses thermal energy for treatment. The short-term results show it to have good outcomes with a potential for outpatient-based treatment preserving sexual function. This review serves to provide an overview of the technique and evaluate its safety and efficacy.